Influência da adição de plasma seminal ao sêmen congelado de jumento (Equus asinus) e da lavagem uterina, sobre a fertilidade de jumentas - Oliveira, Pedro Victor de Luna Freire [UNESP] (2015)
The aim of this study was to evaluate whether the addition of autologous seminal plasma to frozen donkey semen, coupled uterine flushing after artificial insemination influence on fertility rates in jennies. Two experiments were conducted: experiment I, the parameters of sperm kinetics were analyzed by using computer assisted sperm analysis (CASA), analysis of plasma membrane integrity and acrosome (MPAI), lipid peroxidation (PERO) and reactive species content intracellular oxygen (ROS) by the technique of flow cytometry, 15 ejaculated 3 donkeys, diluted in INRA-96® (IC - INRA, IMV Technologies, France) -. Rota et al, (2012) or BotuCrio® (BC - Botupharma, Botucatu, Brazil), with and without addition of seminal plasma (SP) after thawing. The results were similar for CASA to 2 extenders (P> 0.05), however BC provided greater MPAI integrity beyond smaller PERO than the IC, resulting in lower EROS (P <0.05). The addition of PS reduced the parameters of CASA (P <0.05), but no action on the MPAI and Pero (P> 0.05). Experiment II, evaluated the influence of the addition of autologous SP in post-thaw and its association with uterine lavage (L) pos-IA, in the fertility jennies. 86 cycles of 33 jennies were used, divided into 8 groups: G1) BC + SP + Land G2) IC + SP + L, were tested by 14 cycles each; G3) BC+L and G4) IC+ L, were tested on each 11 cycles, all L were made 10 hours after AI; G5) BC + SP and G6) IC + SP were used in 8 cycles each, and the G7) BC and G8) IC were evaluated in 10 cycles each. It was found that the SP, had no effect on fertility jennies (p = 0.6582) however L 10 h post-IA, increased pregnancy rate (p = 0.0097) increasing from 0% (G7 and G8) to 42.9% (G1 and G2)